ETHICS AND THE DYNAMIC VULNERABILITY OF CHILDREN - SCHWEIGER, GOTTFRIED; GRAF, GUNTER (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2017)
In this paper, we want to examine the particular vulnerability of children from an ethical perspective. We want to defend three claims: Firstly, we will argue that children’s vulnerability is best understood as a dynamic quality, meaning that as children progress through childhood, their vulnerability also undergoes particular changes. To capture this, we want to discriminate among physical, mental, social, and symbolic vulnerability, which vary according to certain features, such as age, maturity, gender, and race. These different traits are furthermore important in order to understand what we owe children from an ethical perspective. In a nutshell, children have moral claims not to be harmed and to be protected against threats to their well-being and well-becoming, and these claims have to be explicated via the dynamic vulnerability of children. Finally, we will argue that one of the main issues is to balance the protection of children and their autonomy claims, which both enhance and diminish their vulnerability.